T Follicular Regulatory Cells: Choreographers of Productive Germinal Center Responses - Lu, Yisi; Craft, Joe (Frontiers in Immunology, 2021)
T follicular regulatory cells, or Tfr cells, are a discernable population of regulatory T (Treg) cells that migrate to the B cell follicle and germinal center (GC) upon immune challenge. These cells express the transcription factor Bcl6, the master regulator required for development and differentiation of T follicular helper cells, and are among a group of previously described Treg cells that use T helper cell–associated transcription factors to adapt their regulatory function to diverse milieus for maintenance of immune homeostasis. While there is consensus that Tfr cells control B-cell autoreactivity, it has been unclear whether they regulate productive, antigen-specific GC responses. Accordingly, understanding the regulatory balancing that Tfr cells play in maintenance of B-cell tolerance while optimizing productive humoral immunity is crucial for vaccine-design strategies. To this end, we discuss recent evidence that Tfr cells promote humoral immunity and memory following viral infections, fitting with the accepted role of Treg cells in maintaining homeostasis with promotion of productive immunity, while mitigating that which is potentially pathological. We also propose models in which Tfr cells regulate antigen-specific B cell responses.